# Calc word problem

## Homework Statement

"1. The net change, C, in the energy level of a forging animal over a period of time t is equal to the energy intake, I, minus the energy expended, E: C= I-E
Suppose that the energy intake (per unit time, j>0, is a constant. Then, over a time interval t, the total energy intake is I=jt.
Further, suppose that B is the basal metabolic rate, and f is the energy required for foraging activity per unit time t, (where B, f>0 are constants). Then the total energy required to forage for time t is
E= ft+B.

a) Determine the time at which energy intake I balances energy spent, E i.e the time at which the net change in the energy level is zero.

b) What conditions must be satisfied by the constants f and j (other than f,j>0) defined above for your answer to be biologically meaningful?

## The Attempt at a Solution

a) C= I-E
0=I-E
0=(jt)-E
E/j=t

b) Im not sure what it wants but this is what I did randomly.

E-B/t=f and I/t=j

c) Not sure on what to say due to (b)